An extended dysfunctional area in the congestive area of the remnant liver after hemi‐hepatectomy with middle hepatic vein resection for liver cancers evaluated on the gadoxetic acid disodium‐enhanced magnetic resonance imaging. Issue 1 (20th June 2013) - Mu, Han; Ariizumi, Shunichi; Katagiri, Satoshi; Egawa, Hiroto; Yamamoto, Masakazu
Abstract Background The aim of the present study was to evaluate the liver function in the congestive area of the remnant liver after hemi‐hepatectomy with middle hepatic vein (MHV) resection for liver cancers. Methods From November 2009 through December 2012, 18 patients underwent hemi‐hepatectomy including the MHV for liver cancers. Post‐hepatectomy, the volume of the congestive area, which appeared as a hyper‐intense area on T2‐weighted images and dysfunctional area, which appeared as a low intensity area on hepatobiliary phase images in the remnant liver was evaluated in all patients by gadoxetic acid disodium‐enhanced magnetic resonance imaging. Results Fifteen of 18 patients showed a congestive area, and 16 of 18 patients showed a dysfunctional area in the remnant liver. The dysfunctional rate (median 11%) was significantly larger than the congestive rate (median 5%, P = 0.0004). The dysfunctional rate was associated with tumor invasion to the root of the MHV, and no tumor invasion to the root of the MHV was identified as a significant predictor of a larger dysfunctional area (odds ratio 25.888, P = 0.0267) on multivariate analysis. Conclusion Hemi‐hepatectomy with MHV resection for liver cancers should be performed considering the dysfunctional area in the remnant liver, which is associated with tumor invasion to the root of the MHV.